Macrophytes' Performance in Floating Treatment Wetlands for the Remediation of Ciprofloxacin‐Contaminated Water. Issue 2 (27th December 2022) - Shah, Syed Wajid Ali; Rehman, Mujaddad ur; Anwar, Samina; Hayat, Azam; Shabir, Ghulam; Tahseen, Razia; Rahman, Moazur; Islam, Ejazul; Iqbal, Samina; Afzal, Muhammad
Abstract: The presence of trace antibiotics in domestic and industrial effluents poses a risk of toxicity to fauna and flora. The application of floating treatment wetlands (FTWs) is a low‐cost and sustainable approach to remediate wastewater. In this study, the performance of different macrophytes vegetated in FTWs for the remediation of ciprofloxacin (CIP)‐contaminated water is investigated. Six macrophytes, Brachia mutica, Typha domingensis, Phragmites australis, Canna indica, Cyperus laevigatus, and Leptochloa fusca, are vegetated in FTWs for the removal of CIP (50 mg L −1 ) from water. The FTWs show the potential to remove 30–43.58 mg L −1 CIP from water in 28 days. They also reduce the chemical oxygen demand (118–138 mg L −1 ) and biochemical oxygen demand (35–45 mg L −1 ) of water. Among the macrophytes, C. indica removes maximum (43.58 mg L −1 ) and T. domingensis minimum (30 mg L −1 ) CIP. Canna indica and T. domingensis exhibit the maximum and minimum increase (30% and 12% of dry biomass) in growth, respectively. This study reveals that the FTWs vegetated with different plant species exhibit varying performances in removing CIP from water. This investigation is a step forward toward sustainable bioremediation of water contaminated with antibiotics. Abstract : The presence of antibiotics in water is one of the major threats to the health of living organisms. Here effectiveness of floating treatment wetlands vegetated with macrophytes for remediation of ciprofloxacin‐contaminated water is shown. Among six tested macrophytes, Canna indica exhibits maximum growth in ciprofloxacin‐contaminated water and removal of ciprofloxacin from water.